Influence of Cold Stress on Growth and Flavonoids Accumulation in Artemisia Tilesii "Hairy“ Root Culture - Havryliuk, Olesia; Мatvieieva Nadiia; Tashyrev, Oleksandr; Yastremskaya, Larisa (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The aim of the work was to investigate the effect of short-term cold stress on the growth, antioxidant activity and flavonoids synthesis in the Artemisia tilesii “hairy“ root cultures. The effect of low temperature was studied by roots cultivating during the first 1, 2 and 5 days at +10 °C, then the plants were grown at +24 °C The total flavonoids content in Rutin equivalent was determined spectrophotometrically using alumunium chloride assay. Antioxidant activity of ethanolic extracts was studied using the DPPH method. The root lines differed in sensitivity to short-term temperature decrease up to +10 °C. Stress factor action resulted in a reduction of mass increment in 1.7–3 times. At the same time, two lines were found to be less sensitive to the cold stress since the cultivation for a short period at the low temperatures did not suppress their growth. Transgenic root lines also differed in the flavonoids content which was up 3–15 mg RE/g. Cultivation of “hairy” roots under short-term cold stress has led to decrease of the flavonoids content in all “hairy“ root lines except line No. 5. Cold stress did not lead to the significant changes of antioxidant activity in any of the studied root lines except root line No. 5 where the greater antioxidant activity was observed in one- and two-day cold stress. Thus, short-term cold stress have suppressed the “hairy“ roots growth, inhibited flavonoids accumulation, and had no effect on the antioxidant activity (except one roots line).